The effect of progressive muscle relaxation and nature sounds on blood pressure measurement skills, anxiety levels, and vital signs in nursing students. Issue 4 (26th February 2021) - Korkut, Sevda; Ülker, Türkan; Çidem, Aysun; Şahin, Sevil
Abstract: Purpose: The aim of this study was to determine the effect of progressive muscle relaxation (PMR) and nature sounds (NS) on students' blood pressure measurement skills, anxiety levels, and vital signs. Design and Methods: This randomized controlled study conducted at the nursing department of a university in February 2020. During skill training, one group was given PMR and one group was given PMR + NS. The routine teaching procedure was applied to the control group. Findings: The PMR (37.80 ± 10.1) and PMR + NS (31.19 ± 6.15) groups had lower mean postintervention anxiety scores compared with the control group (40.86 ± 9.13). The PMR + NS group had higher mean postintervention knowledge test score than other. Practice Implications: PMR + NS and PMR helped reduce nursing students' anxiety levels and pulse rates. PMR + NS helped increase their blood pressure knowledge test scores.